Closure-related complications after median sternotomy in cats: 26 cases (2010–2020). Issue 6 (June 2022) - Hennet, Julie; Pilot, Mariette A; Anderson, Davina M; Rossanese, Matteo; Chrysopoulos, Angelos; de la Puerta, Benito; Mullins, Ronan A; Chanoit, Guillaume
Objectives: The aim of this study was to determine closure-related complications and outcome after median sternotomy (MS) in cats. Methods: This was a retrospective, multicentric study. The medical records of cats undergoing MS from six referral hospitals were reviewed (2010–2020). Data retrieved included signalment, history, presenting complaints, surgery, patient outcomes and complications. Follow-up was performed via patient records and email/telephone contact with both owners and referring veterinarians. Descriptive statistics were performed. Results: Data on 36 cats were collected; four were excluded due to insufficient follow-up and six died less than 5 days after surgery. Twenty-six cats survived to discharge (survival rate 81%). Three cats had a full sternotomy (FS) performed and 23 cats a partial sternotomy (PS). Of the cats that underwent a PS, six included the manubrium (PSM) and three included the xyphoid process. For 14 cats, the length of sternotomy was unknown. Sternotomy closure was performed with suture in all cats. Two cats (7.7%) developed closure-related complications, both after PSM, during the long-term follow-up, one mild, slightly displaced sternal fracture and one severe, sternal dehiscence (without skin wound dehiscence) requiring revision surgery. No seroma, surgical site infection or wound dehiscence occurred. The most common reason for MS was the presence of a thoracic mass (17/26; 65%), with thymoma being the most common (11/17; 65%). Conclusions and relevance: MS has a low closure-related complication risk in cats when compared with dogs. Complications in cats present differently to what has been previously described in dogs.